Sustaining Employability Through Work-life Learning Practices and Policies - Billett, Stephen; Salling Olesen, Henning; Filliettaz, Laurent (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book seeks to advance understandings of and approaches to supporting and sustaining working age adults' learning across lengthening working lives and inevitable transitions they encounter and are required to negotiate. It is founded on the processes and findings of a three-phase practical inquiry into worklife learning and its implications for workplace and educations' practice conducted in Australia over a three-year period commencing in 2019. Diverse perspectives and orientations were utilised in approaches to data analysis and renderings from the data, thereby opening up the analysis of these complex phenomena to different lines of interrogation, questions and analytical approaches. It elaborates more fully understandings about the processes of adults' learning and development across their lifespan of adulthood referred to as working life, and what factors and contributions supported that learning. This book also attempts to reconcile a coherent view about development across the work lifespan, and how that can be supported by education provisions, workplaces, communities, and by the adults themselves.
Part One: Worklife learning and employability -- Chapter 1. Adults' worklife learning -- Chapter 2. Policies and practices for sustaining employability through worklife learning -- Part Two: Elaborating and investigating worklife learning -- Chapter 3: The imperatives of and for worklife learning (a review) -- Chapter 4. Investigating learning for employability: Method and procedures -- Part Three: Orientation and perspectives of understanding and elaborating worklife learning -- Chapter 5. Employability and work life history -- Chapter 6. Literate practices in worklife histories, transitions and learning - Laurent Filliettaz -- Chapter 7. Learning and development across worklife transitions -- Chapter 8. Indigenous Australian peoples and work: Examining work-life learning histories of Indigenous Australian workers - Debbie Bargallie -- Chapter 9. Learning across working life: a product of 'personal curriculum -- Chapter 10. Negotiation and work-life transitions -- Chapter 11. Contributions of tertiary education -- Chapter 12. Worklife transitions and learning across working life: An Australian survey -- Part Four: Consolidations and differentiations -- Chapter 13. Consolidations and differentiations -- Chapter 14. Worklife learning: conceptual advances and expanding explanatory bases.
Keywords: Continuing education; Adult education; Professional education; Vocational education; Lifelong Learning; Adult Education; Professional and Vocational Education